1977
DOI: 10.1152/ajpendo.1977.233.3.e208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lumenal contents on colonic cell replacement.

Abstract: Recent studies have shown that the rate of colonic cell renewal can be altered through fasting and refeeding, which produces a marked depression and transient stimulation, respectively. In the present study, the role of physical versus nutritional stimulation in the colonic fasting-refeeding response and the renewal of the functional colonic compartment were evaluated via a nondestructive colonic ligation procedure. The results reported herein suggest that physical stimulation by lumenal factors is in part req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

1979
1979
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 10 publications
1
15
1
Order By: Relevance
“…First, dietary constituents independent of bacteria can alter colonic mucosal growth characteristics. Second, the presence of bacteria in and of themselves do not pro- (15,54,60). The findings in our study support this because the inclusion of 5% or more dietary fiber in the diet of germ-free animals resulted in a mild, but significant, increase in mucosal volume.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…First, dietary constituents independent of bacteria can alter colonic mucosal growth characteristics. Second, the presence of bacteria in and of themselves do not pro- (15,54,60). The findings in our study support this because the inclusion of 5% or more dietary fiber in the diet of germ-free animals resulted in a mild, but significant, increase in mucosal volume.…”
Section: Introductionsupporting
confidence: 68%
“…The growthpromoting effect of increased colonic content mass may be mediated through increased stretch or tension that occurs in the colonic wall as increased mass is moved through the colon. Other studies have shown that the stretching of mucosal tissue in the colon and other epithelial sites is capable of inducing proliferation in epithelial cells (7,10,40,54). The observation in this study that there were not consistent differences in the subjective assessment of mucosal thickness between diet groups (42).…”
Section: Introductioncontrasting
confidence: 50%
“…The method is applicable to normal colon of animals at any age and its application to grafts of foetal mouse colon has allowed definition of the effects of several factors on cell kinetics. The experimental situations examined here-of normal post-natal growth, of antigen-free growth in isografts, and the effects of cell-mediated immunity-parallel those examined in a previous morphological study (Holden and Ferguson 1976 (Dowling et al, 1967;Stragand and Hagemann, 1977). Alternatively, immune reactions between mucosal lymphoid tissues and antigens present in food or bacteria in the bowel lumen may be the initiating factor causing the rise in cell turnover.…”
Section: Discussionmentioning
confidence: 80%
“…It is well known that gut wall distention by the luminal contents stimulates epithelial cell proliferation in the gut [6,7], gallbladder [8], uterine [9] and skin [10]. We speculated that gut wall stimulation by a hard stomach curd, the formation of which occurs with milk formulas based on casein, might be one cause of gut hypertrophy, since the hardness of the stomach curd could depend on the casein-towhey protein ratio in the milk.…”
Section: Introductionmentioning
confidence: 99%